The effect of the achievement motivations on sport character. An investigation on elite athletes - Yildiz, Y.; Dinc, F. (International Journal of Applied Exercise Physiology, 2021)
This study aimed to evaluate the sport character orientation of elite athletes in different branches of Turkish National Teams in terms of their achievement motivation. Two scales were used to obtain data for this study.To measure the sport character of the athletes, the "Sport Character Scale" developed by Chang-Yong Jang (2013) and adapted to Turkish by Görült and Tuncel (2017) was used. The "Sports-Specific Achievement Motivation Scale" developed by Willis (1982) and adapted to Turkish by Tiryaki and Gödelek (1997) was used to measure the motivation of athletes` success. Descriptive statistics, normality tests, correlation analysis, and multiple regression analyzes were performed by using the SPSS 25.0 package program in the analyses of the data. According to demographic findings, the majority of 223 athletes participating in the study were male athletes (70.9%). The majority of athletes (54.7%) were 21-24 years old, 79.8% of them were interested in team sports; 43.5% of them were national athletes between 4-6 years. In addition, the majority of the athletes (33.2%) had the best Balkan Ranking. The normality test results revealed that skewness-kurtosis coefficients of the variables were between ±3.0 and showed a normal distribution. The mean of the variables was "2.54" to "4.17"; the standard deviation was between "0.55" and "1. 02". Multiple regression analysis results showed that the relationship between variables was statistically significant (p<0.01). As a result, this study showed that there is a statistically significant relationship between sport character and "self-confidence", "motive to achieve success", "power motive", and "external factor approach". In addition, it was observed that "motive to achieve success" and "power motive" predicted the sport character by approximately 38%.